Memristor based BPSK and QPSK demodulators with nonlinear dopant drift model. (October 2016) - Elashkar, N.E.; Aboudina, M.; Fahmy, H.A.H.; Ibrahim, G.H.; Khalil, A.H.
Abstract: In this paper, the dependence of the instantaneous memristance value and its I–V characteristics on a periodic signal phase are studied. Hence, expression for the instantaneous memristance as a function of the periodic input phase is derived. This derivation is based on the memristor linear dopant drift model and is provided for sinusoidal input waveforms. To prove the tendency, simulations using linear and nonlinear dopant drift memristor models are performed in the Cadence simulation environment. Based on those, a set of digital communication demodulators are proposed and investigated exploiting the change of the average memristance with the initial phase of applied signal. The experimental-based 'nonlinear' dopant drift model is used in designing the proposed demodulators for Binary Phase Shift Keying (BPSK) and Quadrature Phase Shift Keying (QPSK) modulation schemes. Since all proposed demodulators are asynchronous, the proposed circuits do not need any carrier recovery circuits. Moreover, transient simulations have been executed showing the proper matching to the expected performance.